The Relationship between frequency and satisfaction of leisure participation and health-related quality of life in women with fatigue secondary to chronic illness - Khemthong, Supalak (Curtin University, 2007)
Fatigue secondary to chronic illness (FSCI) is a common experience in individuals with chronic conditions, with fatigue impacting on performance of daily activities and health-related quality of life (HRQoL). Due to the higher prevalence of FSCI in women, they may experience even greater disruption to roles and activity engagement. The literature consistently points to three main aspects when defining fatigue regardless of diagnoses; a physical aspect, a psychological aspect, and the impact on activity and participation. Research into the first two aspects has demonstrated relationships between fatigue, pain, depression, and social support. However, examination of the third aspect has been largely overlooked with respect its relationship to, and impact on, fatigue. Leisure theorists have hypothesized that engagement in leisure activities makes a positive contribution to physical and mental health. Previous research has measured leisure activities based on frequency of, or satisfaction with, participation. While some research has shown that physical and social activities have positive health benefits, gaps still exist in understanding the relative contribution of different types of leisure participation to fatigue and HRQoL.For example, little research has examined the contributions of leisure participation and leisure satisfaction to HRQoL and fatigue in women with chronic conditions. One explanation for the lack of research may be the absence of measurement tools developed to classify and quantify participation in different types of leisure activities for women with FSCI. Without a measurement tool, the relative contribution of participation in different activities (by frequency and/or satisfaction) to fatigue and HRQoL cannot be examined.This PhD research aimed to fill the current gaps in understanding different types of leisure participation in related to fatigue and HRQoL. It sought to address two component parts: development and testing of the Classification of Leisure Participation (CLP) Scale; and an examination of the contribution of leisure participation to fatigue and HRQoL in women with FSCI.